Taxonomy, distribution, natural history and conservation of the Russet-mantled Foliage-gleaner Syndactyla dimidiata (Pelzeln, 1859) (Aves: Furnariidae) - Lopes, Leonardo Esteves; Gonzaga, Luiz Pedreira (Zootaxa, 2014)
Russet-mantled Foliage-gleaner is an extremely poorly known species, the range of which is centered in the Brazilian Cerrado, where it inhabits riparian forests. Two subspecies are recognized, but the limits of their ranges are controversial. Furthermore, it was recently suggested that the species is one of the few in the family Furnariidae to show sexual dichromatism. In this paper we examined the plumage coloration and morphometrics of 33 study skins (85% of the available specimens). We conclude that the geographic variation and sexual dichromatism reported for S. dimidiata originated from misinterpretation of the plumage variation observed in this species, which is best considered monotypic. We also present natural history data on Russet-mantled Foliage-gleaners and suggest considering it a globally Vulnerable species.